The Escalating Competition Faced by Netflix - Jin Sun Ahn; Jung Hoon Kim; Youngbin Kim; Jaeseong Lim (Journal of Accounting, Business and Management (JABM), 2023)
Netflix is the biggest over-the-top media service company in the world. It provides video on demand to its paid subscribers. As of December 2021, the company has 222 million paid subscribers in more than 190 countries. The ongoing global pandemic has boosted Netflix’s revenues and profits as people have spent more time indoors. However, the growing popularity of video-on-demand services has encouraged significant competition from other providers. This paper describes how escalating competition may affect Netflix’s business model.